Final Diagnosis of Solitary Thyroid Nodule: Cytology, Histology or Molecular Genetics? - De Silva, Chandu (Faculty of Medicine, University of Colombo, 2020)
Fine needle aspiration (FNA) is an essential preliminary investigation in the investigation of a solitary thyroid neoplasm ...